Anaphylaxis due to thiamine disulfide phosphate, a derivative of vitamin B1; a case report and literature review - Amano, Asuka; Takahagi, Shunsuke; Kinoshita, Hitomi; Nakamura, Rie; Ishii, Kaori; Hide, Michihiro (Allergology International, 2022)
[Dear Editor, ] Vitamin B1 is an essential substance for living organisms, which acts as a coenzyme in the metabolic pathway of glucose and amino acids. Vitamin B1 includes the natural and artificial forms ; the former (natural vitamin B1) can be ingested from food, and the latter (vitamin B1 derivative) is artificially synthesized by modifying its structure. Several artificial forms of vitamin B1 are used as a therapeutic preparation in patients' care. Thiamine disulfide phosphate (TDSP) is a vitamin B1 derivative, in which the thiazole nucleus in the natural vitamin B1 (thiamine) is cleaved to maintain a higher blood concentration than natural vitamin B1, and high potential of tissue penetration. Although a few cases of type I hypersensitivity to natural vitamin B1 have been reported, no reports on type I hypersensitivity to vitamin B1 derivatives exist in the English-language literature. Here, we report a case of anaphylaxis caused by the intravenous injection of TDSP, in which a histamine release test (HRT) using the patient's basophils was useful for its diagnosis.